FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN PRINSIP ENAM TEPAT PEMBERIAN OBAT - Haryani, Sri (JURNAL MEDIA KESEHATAN, 2015)
The drug is one of the most important part of the healing process, healthrestoration and also prevention of a disease. The preparation and administration of drugsshould be done accurately by nurses. JCHO data obtained also showed that 44,000 of the98,000 deaths that occur in hospital every year due to medical errors. Objective Todetermine what factors are associated with the application of the principle of the rightdrug at the hospital six Curup 2014. The method used is descriptive cross sectionalAnalytical approach. Research done in the area of obstetrics and children's hospitalsCurup on April 1 - April 14, 2014. This study use total sampling technique that is 35person. Data collection tool used was a questionnaire and observation sheet. Applicationof the principle of the right drug at the hospital six Curup majority of respondents 23(65.7%) applying the principle of "Six Right" exactly. There is no relationship betweenage, education, and knowledge of the proper application of the six principles ofmedicine. But, there is a relationship between length of employment with the properapplication of the six principles of medicine. It is expected that the hospitaladministration can oversee the implementation of the six principles right.